INTEGRASI ARTIFICIAL INTELLIGENCE DALAM DESAIN PEMBELAJARAN AKIDAH AKHLAK UNTUK MENINGKATKAN PERSONALISASI BELAJAR DAN AKHLAK DIGITAL DI MTSN 2 PONTIANAK - ’Abidah, Nur; Wahab, Wahab (Jurnal Visi Ilmu Pendidikan, 2026)
The development of Artificial Intelligence (AI) in education provides new opportunities for adaptive and personalized learning. This study aims to design and test an AI-based Islamic Religious Education (Akidah Akhlak) learning model that enhances personalized learning and digital ethics formation among eighth-grade students at Madrasah Tsanawiyah Negeri 2 Pontianak. The research applies a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The participants consist of 32 purposively selected students. The results reveal that AI-based Akidah Akhlak learning design increases personalized learning by 35% and strengthens key digital ethics indicators such as honesty, responsibility, and self-control. The integration of AI reinforces the teacher’s role as an ethical overseer to ensure moral and Islamic value alignment in technology use.